2017
DOI: 10.1186/s13017-017-0135-4
|View full text |Cite
|
Sign up to set email alerts
|

The rate of success of the conservative management of liver trauma in a developing country

Abstract: BackgroundThe conservative treatment of liver trauma has made important progress over the last 10 years at the Trauma University Hospital in Tirana, Albania. The percentage of success was 58.7%. The aims of this study were to analyze the conservative treatment of liver trauma and to compare the results with those in the literature.MethodsThis study was conducted prospectively from January 2009 to December 2012. We analyzed 173 patients admitted to our hospital with liver trauma. Liver injuries were evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
1
21
0
7
Order By: Relevance
“…CT scan may help in subsequent Table 3 AAST liver trauma classification [24][25][26][27][28][29][30][31][32]. Diagnostic peritoneal lavage (DPL) should be considered diagnostic modality in low-resource settings, where CT scan or US is not promptly available [33]. It should be considered in the presence of massive subcutaneous emphysema in a shocked patient in whom ultrasound cannot be done and/or in the presence of free peritoneal fluid without solid organ injury in a hemodynamically stable patient.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…CT scan may help in subsequent Table 3 AAST liver trauma classification [24][25][26][27][28][29][30][31][32]. Diagnostic peritoneal lavage (DPL) should be considered diagnostic modality in low-resource settings, where CT scan or US is not promptly available [33]. It should be considered in the presence of massive subcutaneous emphysema in a shocked patient in whom ultrasound cannot be done and/or in the presence of free peritoneal fluid without solid organ injury in a hemodynamically stable patient.…”
Section: Diagnosismentioning
confidence: 99%
“…It should be considered in the presence of massive subcutaneous emphysema in a shocked patient in whom ultrasound cannot be done and/or in the presence of free peritoneal fluid without solid organ injury in a hemodynamically stable patient. The possibility of DPL-related complications (up to 2%) should be considered [33].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Bucirt et al have reported that liver injuries that was inspected during laparotomy for associated injuries had no active bleeding. 21 Richardson et al, commented that many experienced trauma surgeons apply surgical treatment for stable traumatic liver injury patients and it will have a positive impact on their survival. However, such a comment was not applicable to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Blunt liver trauma can be mild, moderate or severe. Mild and moderate liver trauma can be managed conservatively without surgery [3,11,15,18].…”
Section: Conservative Treatment Of Liver Traumamentioning
confidence: 99%